Pengaruh Beban Kerja Terhadap Kinerja Pegawai di Bagian Kesejahteraan Rakyat Sekretariat Daerah Kabupaten Buru Selatan - Halija Loilatu; Hendro Triyono; Kitfirul Aziz Raharjo; Andri Setiawan (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to examine the effect of workload on employee performance in the Public Welfare Division of the Regional Secretariat of South Buru Regency. The method used is a quantitative approach with simple linear regression analysis and validity and reliability tests of the instruments. Data were collected through questionnaires based on workload and employee performance indicators, with a sample of 52 employees out of a total population of 60. The analysis results show that all instruments are valid and reliable, and there is a significant negative relationship between workload and employee performance. The coefficient of determination of 17.1% indicates that workload significantly contributes to the variability of employee performance, followed by the positive influence of other unmeasured variables. These findings highlight the importance of effective workload management to improve employee performance and optimize public service delivery. The results of this study provide an empirical basis for policymakers in designing better human resource management strategies.